SAT0045 A NOVEL SMALL MOLECULE, MBS2133, MODULATES OSTEOCLAST PRE-CURSOR METABOLISM TO INHIBIT OSTEOCLAST DIFFERENTIATION: AN ALTERNATIVE THERAPY FOR OSTEOLYTIC PATHOLOGY IN RA. (June 2019) - Sood, Shatakshi; Patel, Lisa; Foster, Martyn; Jopling, Louise; Hof, Rob Van't; Greig, Iain; Williams, Sam; Mcinnes, Iain; Goodyear, Carl
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease associated with substantial local and systemic bone loss. Despite the availability of several treatment options many patients do not reach low disease activity. Furthermore, current therapeutics generally target inflammation rather than erosive pathology. Thus, there remains a need for new therapies that can target both aspects of the disease. Prior studies have shown that biphenylcarboxylic acid small molecule derivatives not only inhibit murine osteoclastogenesis but also attenuate inflammation and bone destruction in murine models of RA 1, 2 . Objectives: To evaluate a novel small molecule derivative, MBS2133, on human osteoblastogenesis, osteoclastogenesis and cellular function, and to investigate the in vitro mechanism-of-action. Methods: Osteoblasts were derived from human mesenchymal stem cells. Cells were differentiated in the presence or absence of MBS2133 and mineralization assessed by Alizarin Red staining. Human CD14 + blood monocytes were differentiated into osteoclasts (OCs) with M-CSF and RANK-L, in the presence or absence of MBS2133, and/or metabolites. Mature OCs were stained with tartrate-resistant acid phosphatase (TRAP) and quantified by light microscopy. Osteolytic activity was assessed on mineral-coated surfaces. Western blot analysis was used to assess downstream signalling pathways. Changes in the metabolic profile of pre-osteoclasts following 4h exposure to MBS2133 was carried out by liquid chromatography mass spectrometry. Results: MBS2133 had no effect on the differentiation and function of primary human osteoblasts. In comparison, exposure of RANK-L stimulated CD14 + monocytes to MBS2133 significantly reduced OC differentiation and osteolytic activity of mature OCs. Notably, exposure of pre-OCs to MBS2133 for 2h at initiation of osteoclastogenesis, was sufficient to significantly reduce subsequent OC differentiation. Evaluation of treated pre-osteoclasts revealed that RANKL-mediated phosphorylation of p38 was reduced. Metabolomic analysis of pre-osteoclasts revealed that MBS2133 induced a substantial reduction in a range of metabolites associated with glycolysis, oxidative phosphorylation and fatty acid oxidation pathway. Notably, L-carnitine, which facilitates the transportation of fatty acids to the mitochondrial matrix and enables processing and entry into tricarboxylic acid (TCA) cycle for further energy production, was significantly reduced. In vitro supplementation of L-carnitine inhibited the ability of the compound to switch off OC differentiation and osteolytic activity. Conclusion: The results of this study demonstrate that MBS2133 specifically modulates the metabolome of myeloid cells, which has a substantial impact on their ability to differentiate into mature osteoclasts. These findings highlight the importance of modulating the glycolysis/oxidative phosphorylation axis in osteoclastogenesis and suggest that targeting the metabolic state of pre-osteoclasts could offer a new therapeutic approach to treat bone resorption in rheumatic diseases. References: [1] Greig IR, et al. Development and Characterization of Biphenylsulfonamides as Novel Inhibitors of Bone Resorption. J.Med.Chem. 2006;49:7487–7492 [2] Coste E, et al. Identification of small molecule inhibitors of RANKL and TNF signalling as anti-inflammatory and antiresorptive agents in mice. AnnRheumDis2015;74:220–6. Disclosure of Interests: Shatakshi Sood: None declared, Lisa Patel Shareholder of: Shareholder of Istesso Ltd, Employee of: Employee of Istesso, Martyn Foster Shareholder of: AstraZeneca, Consultant for: Istesso, Levicept, Employee of: AstraZeneca, Louise Jopling Shareholder of: Johnson and Johnson (employee), Employee of: Employee of Janssen (Pharmaceutical arm of Johnson & Johnson) since May 2008 to present day, Rob van't Hof Shareholder of: OsteoRx Ltd, Iain Greig Shareholder of: Shareholder in OsteoRx Ltd, a spin-out company from the University of Aberdeen, which retains a financial interest in MBS2133, Sam Williams Shareholder of: Shareholders of Istesso Ltd, Employee of: Employees of Istesso, Iain McInnes Grant/research support from: AstraZeneca, Celgene, Compugen, Novartis, Roche, UCB Pharma, Consultant for: AbbVie, Celgene, Galvani, Lilly, Novartis, Pfizer, UCB Pharma, Carl Goodyear Grant/research support from: AstraZeneca, BMS, Celgene, Janssen, MedAnnex, Pfizer and UCB, Speakers bureau: Abbvie